Quantitative trait loci mapping in plant genetics by [alpha]-design experiments and molecular genetic marker systems - Wolfgang Urfer; S. Mejza; F. Hering (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1999)
Research concerning the quantitative trait loci (QTL) mapping in plant genetics usually consists of two stages. The first stage is concerned with collecting data while the second one, based on the data collected, is concerned with a proper QTL study. The final inferences are strictly connected with the quality of the two approaches applied in both stages. Data to be analyzed come from an experiment dealing with offsprings obtained from a crossing system of several lines. The genotypes then are observed in some natural or quasi natural environment. The QTL studies are based on so called genotype adjusted means. In a-designs the adjusted means can be calculated in many ways, which will be presented in this paper. We also give an EM-algorithm for the estimation of genetic parameters and comment on recent biometrical research in molecular plant genetics. Finally we mention some activities in the new field of bioinformatics.
Keywords: 519